Third-order optical nonlinearity in silicon nitride films prepared using magnetron sputtering and application for optical bistability - Ding, Baoyong; Yu, Xiuru; Lu, Heng; Xiu, Xianwu; Zhang, Chao; Yang, Cheng; Jiang, Shouzhen; Man, Baoyuan; Ning, Tingyin; Huo, Yanyan (Journal of applied physics, 2019)
We investigate the third-order optical nonlinearity in silicon nitride (SiN) films prepared using magnetron sputtering. The large nonlinear refractive index n2 in SiN prepared at room temperature of a value of −2.00 × 10−16 m2/W and the nonlinear absorption coefficient β of 1.44 × 10−9 m/W are determined by the Z-scan method at a wavelength of 1064 nm and a pulse duration of 25 ps. The n2 is three orders of magnitude larger than that in SiN films prepared by the chemical vapor deposition method and at a wavelength of 1.55 μm. The enhanced n2 up to −6.27 × 10−16 m2/W and the slightly changed β, indicating an enhanced ratio of |Reχ(3)|/|Imχ(3)|, are further obtained in the annealed samples. Such a change is probably due to the crystallization of the films. The optical bistability in SiN resonant waveguide grating (RWG) is numerically studied. The low threshold intensity around 300 MW/cm2 in the RWG is obtained.